The Theory of Endowment, Intra-industry and Multi-national Trade. - Markusen, J; Venables, A (2000)
We develop a monopolistic-competition model of international trade which includes positive trade costs and endogenous multinational firms. We demonstrate how the presence of trade costs changes the pattern of trade, creates incentives for factor mobility which may lead to agglomeration of activity in a single country, and may lead to multinational firms. The mix of national and multinational firms that operate in equilibrium depends on technology and on the division of the world endowment between countries. Multinationals are more likely to exist the more similar are countries in both relative and absolute endowments, a result consistent with empirical evidence. The presence of multinationals creates trade in headquarters' services, alters the incentives for factor mobility, and reduces the tendencies towards agglomeration.